2022
DOI: 10.1039/d2cc03362c
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced Li extraction from LiMn2O4/TiO2 in a water-in-salt electrolyte for photo-rechargeable batteries

Abstract: Photocharging of spinel LiMn2O4 has been demonstrated by utilizing a water-in-salt electrolyte with an electron acceptor and TiO2 nanoparticles, which paves the way for developing high-potential cathode materials for photo-rechargeable batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The discharge capacities from around 1.0 V vs. Ag/AgCl clearly indicate the redox reactions of the Mn-based spinel-oxide cathode materials. 17 As demonstrated here, spinel oxides modified from LiMn 2 O 4 were successfully photocharged, for what we believe is the first time.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…The discharge capacities from around 1.0 V vs. Ag/AgCl clearly indicate the redox reactions of the Mn-based spinel-oxide cathode materials. 17 As demonstrated here, spinel oxides modified from LiMn 2 O 4 were successfully photocharged, for what we believe is the first time.…”
supporting
confidence: 52%
“…The water-in-salt electrolyte enables the charging/discharging of Mn-based spinel oxides due to its high oxidative stability. 17,21 Note that Mn-based spinel cathode materials exhibit multiple redox potentials, 18,25 i.e. , so-called 3, 4, and 5 V regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, modifying the crystal structure of ZnMnO 3 with these elements would be a promising way to improve its cathode performance. In addition, spinel-oxide cathode materials have been employed in many kinds of advanced rechargeable battery systems such as Zn-ion batteries, Li–Mg dual-cation batteries, , and Li-ion photorechargeable batteries . We therefore hope this work provides basic guidelines for understanding the relationship between the phase stability and electrochemical properties of spinel oxides and helps develop future advanced materials.…”
Section: Resultsmentioning
confidence: 99%
“…To explore a high-potential PSC, Kohei Shimokawa et al reported the preparation of TiO 2 /LiMn 2 O 4 , where TiO 2 nanoparticles were the photoactive material responsible for photovoltaic conversion, and LiMn 2 O 4 was for energy storage. 63 Once illuminated by UV-visible light, the photo-generated electrons within TiO 2 were transferred from HOMO to LUMO. The HOMO energy level for TiO 2 was high enough to extract Li + cations from LiMn 2 O 4 .…”
Section: Multi-components Photoelectrochemical Storage Materialsmentioning
confidence: 99%